Fear of COVID-19, stress, anxiety, depression, and insomnia among undergraduate nursing students in Oman - Mohammed Al Maqbali; Mahmoud Alsaraireh; Mohamad AlMekkawi; Omar Melhem; Ibrahim Bashayreh (Tehran University of Medical Sciences, 2023)
Background & Aim: The emergence of COVID-19 has created fears, worries, and anxiety among individuals worldwide. This study aimed to describe the prevalence of mental health problems (fear, stress, anxiety, depression, and insomnia) and their contributing factors among undergraduate nursing students in Oman two years after the start of the pandemic. Methods & Materials: A cross-sectional study was employed for this study. The questionnaire was distributed electronically via Qualtrics® Online survey software. It consisted of items relating to detailed demographics, background history, and standard scales, including the Fear of COVID-19 Scale, the Perceived Stress Scale, the Hospital Anxiety and Depression Scale, and the Insomnia Severity Index. Results: The sample comprised 548 nursing students. The participants had a mean FVC-19 score of 16.39, with a standard deviation of 6.04. The overall prevalence of stress, anxiety, depression, and insomnia among nursing students was 94%, 70%, 53%, and 38%, respectively. There was a significant relationship between fear of COVID-19 (p< 0.05) and stress, anxiety, depression, and insomnia. Conclusion: Fear of COVID-19, stress, anxiety, depression, and insomnia pose notable challenges for undergraduate nursing students. Identifying these mental health issues early is crucial as well as introducing preventive and supportive interventions tailored to the specific contributing factors. This is essential to mitigate the potential for more severe psychological consequences among nursing students.